Elimination of Inter-Institutional Discrepancies in Health Check-up Results: Standardization of Diagnostic Decision Level and Uniformity of Examination Data - Tamura, M. (Methods of Information in Medicine, 1998)
In Japan, more people are taking AMHTS and the number of medical institutions where it is provided is also increasing. AMHTS is expected to continue to expand in scope and importance from now on. People do not necessarily take AMHTS at the same medical institutions year after year. For AMHTS to be truly useful from the viewpoint of preventive medicine and be able to continue its development, it is imperative that the level of diagnosis be standardized and the compatibility of examination data be established among different institutions.The Japan Society of MHTS is conducting pilot studies of reversed quality control (RQC) as part of its activities with the aim of clearly understanding inter-institution gaps regarding AMHTS and to establish uniformity in examination data.
Keywords: Inter-institutional Discrepancies; Reversed Quality Control; Common Unit; Quality Management; Reference Interval